Efficient synthesis of 5-ethoxymethylfurfural from biomass-derived 5-hydroxymethylfurfural over sulfonated organic polymer catalyst. Issue 6 (18th January 2021) - Xiang, Yanping; Wen, Sha; Tian, Yi; Zhao, Kangyu; Guo, Dongwen; Cheng, Feng; Xu, Qiong; Liu, Xianxiang; Yin, Dulin
Abstract : The sulfonic acid grafted porous organic nitrogen-containing polymer (PDVTA-SO3 H) exhibited excellent catalytic activity in the synthesis of 5-ethoxymethylfurfural (EMF) from 5-hydroxymethylfurfural (HMF). Abstract : Herein, we investigated catalytic potential of a functionalized porous organic polymer bearing sulfonic acid groups (PDVTA-SO3 H) to the etherification of 5-hydroxymethylfurfural (HMF) to 5-ethoxymethylfurfural (EMF) under solvent-free conditions. The PDVTA-SO3 H material was synthesized via post-synthetic sulfonation of the porous co-polymer poly-divinylbenzene- co -triallylamine by chlorosulfonic acid. The physicochemical properties of the PDVTA-SO3 H were characterized by FT-IR, SEM, TG-DTG, and N2 adsorption isotherm techniques. PDVTA-SO3 H had high specific surface area (591 m 2 g −1 ) and high density of –SO3 H group (2.1 mmol g −1 ). The reaction conditions were optimized via Box–Behnken response surface methodology. Under the optimized conditions, the PDVTA-SO3 H catalyst exhibited efficient catalytic activity with 99.8% HMF conversion and 87.5% EMF yield within 30 min at 110 °C. The used PDVTA-SO3 H catalyst was readily recovered by filtration and remained active in recycle runs.